2013
DOI: 10.1177/1098612x13509996
|View full text |Cite
|
Sign up to set email alerts
|

Partial parasagittal patellectomy: a novel method for augmenting surgical correction of patellar luxation in four cats

Abstract: We describe a novel surgical technique used to correct feline patellar luxation (PL) where abnormal patellar tracking persists despite conventional corrective surgery. An anatomical difference between feline and canine stifles is that the feline patella is wider relative to the trochlear sulcus. This results in less constrained patellar tracking. Therefore, patellar subluxation is common in normal cats. It was noticed that in some feline cases with clinically significant PL, PL persisted intraoperatively despi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Femoral trochleoplasty is a recommended technique for surgical treatment of patellar luxation. 1,2 However, a recent publication questioned its benefit as it did not correct patellar luxation in four cats 3 ; in that report, intraoperative assessment of the stifle revealed that following trochleoplasty, the patella rode the trochlear ridges instead of tracking in contact with the recessed sulcus. This was thought to be a consequence of the flat and wide shape of the feline patella and was addressed with bilateral partial parasagittal patellectomy (PPP).…”
Section: Introductionmentioning
confidence: 99%
“…Femoral trochleoplasty is a recommended technique for surgical treatment of patellar luxation. 1,2 However, a recent publication questioned its benefit as it did not correct patellar luxation in four cats 3 ; in that report, intraoperative assessment of the stifle revealed that following trochleoplasty, the patella rode the trochlear ridges instead of tracking in contact with the recessed sulcus. This was thought to be a consequence of the flat and wide shape of the feline patella and was addressed with bilateral partial parasagittal patellectomy (PPP).…”
Section: Introductionmentioning
confidence: 99%
“…Partial parasagittal patellectomy was necessary in all four surgeries described in this case series in order to establish patellar tracking in contact with the recessed sulcus and to stabilize the patella. This technique has been previously reported clinically, 24 and was shown to improve the depth of patellar recession over that achieved with block recession trochleoplasty alone in a cadaveric study using CT. 55 The feline patella is relatively wider than the feline femoral trochlear sulcus, 56 and ex vivo studies in cats have shown that following block recession trochleoplasty alone, the feline trochlea becomes too narrow to accommodate it. 55 Instead, the patella rides the trochlear ridges and loses contact with the trochlear sulcus.…”
Section: Discussionmentioning
confidence: 75%
“…As such, partial parasagittal patellectomy was performed as previously described to achieve appropriate patellar tracking. 24 , 46 A TTTA was completed in a standard fashion 41 using a 6 mm cage, two-prong plate and 4 mm spacer (TTA; KYON) with the following modifications: (1) owing to the paucity of bone stock available for screw purchase, in the cranial ear of the cage a 2.0 mm screw with a washer was applied rather than the 2.4 mm screw conventionally placed; (2) no Kirschner wire was used to maintain lateralization of the osteotomised tibial tuberosity; and (3) to lateralize the tibial tuberosity, a titanium spacer (TTA; KYON) was used beneath the cranial cage ear instead of a recessed notch caudally ( Figure 1c ).…”
Section: Case Series Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feline patellar luxation is often treated with a combination of tibial crest translocation (TCT), trochlear sulcoplasty, retinacular overlap, soft tissue release, antirotational suture placement and corrective femoral osteotomy (Scott & McLaughlin 0010). Partial parasagittal patellectomy is described to allow the relatively broad feline patella to recess into a relatively narrow sulcoplasty (Rutherford & Arthurs 8).…”
Section: Introductionmentioning
confidence: 99%